Styles of Management in Russian Retail Company - Burman, Ksenia; Šikýř, Martin, 1974-; Němec, Otakar; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
The goal of my bachelor thesis is to analyze aplied management style of CEO of chosen russian retail company, to identify advantages and disadvantages of applied leadership style in comparison with theory and recommend appropriate measures to improve identified failiures in the company.
Vedoucí práce: Martin Šikýř
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses